Effectiveness of the Scientifically based Flipped Classroom Model to Increase Students' Critical Thinking Ability - Ngadimin, Ngadimin; Hamid, Abdul; Sahara, Yuni; Musdar, Musdar (Universitas Syiah Kuala, 2024)
In fact, the physics learning process in senior high schools does not encourage students to think critically, resulting in low learning outcomes. This research aims to test the effectiveness of a scientific-based flipped class model to enhance students' critical thinking abilities. The research method used is a quantitative method with a quasi-experimental design, specifically nonequivalent pre-test post-test control group design. The population of this study consists of all tenth-grade science classes at Kutacane State Senior High School 3, and the sampling technique used is total sampling, where tenth-grade science class I serves as the experimental group, while the tenth-grade science class II serves as the control group. The instruments used are observation sheets, tests, and questionnaires. Data were analyzed using the N-Gain test, the classical completeness test, and student response analysis. The results of the study showed that critical thinking skills, as measured by both the classical completeness test and N-Gain test, improved in both classes, with the experimental class showing a high gain index category, while the control class showed a moderate gain index category. Learning using a scientific-based flipped class model is effective in enhancing students' critical thinking abilities because it can facilitate students in accessing the provided learning materials.